Analisis Pengendalian Kualitas Produk Roti untuk Menurunkan Reject Rate Menggunakan Metode DMAIC dan Poka Yoke (Studi Kasus: Toko Roti Tous Les Jours) - Yongky Pranata; Suparjo Suparjo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The food and beverage industry in Indonesia continues to grow rapidly, including in the bakery sector. Tous Les Jours Bakery is one of the industry players facing challenges related to a high product defect rate (reject rate) in its production process. Defective products cannot be resold, resulting in financial losses and resource waste. Therefore, this study aims to identify and reduce the reject rate using the DMAIC (Define, Measure, Analyze, Improve, Control) method and Poka Yoke. Measurements taken from September 2023 to February 2024 show an average DPMO of 9,555.93 and a sigma level of 3.844. Donut and regular bread categories contributed approximately 65% of the total defects. Accordingly, improvement recommendations were proposed for these two categories, including the use of timers, automatic molds, temperature sensors, and standardized procedures for proofing, frying, and baking processes.